2013
DOI: 10.1245/s10434-013-3103-6
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Minimally Invasive Versus Open Esophagectomy for Esophageal Cancer

Abstract: MIE is cost-effective compared to open esophagectomy in patients with resectable esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…However, as discussed above, MIE is associated with less morbidity, fewer respiratory complications, reduced hospital stay and better health‐related quality of life than OE . To date, only one study evaluated the cost‐effectiveness of MIE compared with OE . The study found that MIE was less costly and more effective than OE; MIE was estimated to cost $1641 less than OE with an incremental gain in quality‐adjusted life‐years of 0.022.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as discussed above, MIE is associated with less morbidity, fewer respiratory complications, reduced hospital stay and better health‐related quality of life than OE . To date, only one study evaluated the cost‐effectiveness of MIE compared with OE . The study found that MIE was less costly and more effective than OE; MIE was estimated to cost $1641 less than OE with an incremental gain in quality‐adjusted life‐years of 0.022.…”
Section: Discussionmentioning
confidence: 99%
“…MIE consumes longer operation time because of the technical complexity. Further studies are necessary to determine the clinical impacts of longer surgical time . Towards this end, two randomized controlled studies that are currently being performed are assessing the efficacy, risk, life quality and cost‐effectiveness of OE and MIE in resectable oesophageal cancer patients .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little data on economic outcomes of MIE and hybrid procedures compared to traditional approaches. The scant published data suggest MIE may result in decreased or similar costs [12]. A 2009 European study of MIE and open Ivor Lewis esophagectomy reported similar costs and safety, but this report was not adjusted for cost confounders in their analysis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, one of the advantages of MIE is better cost-effectiveness. Lee et al [27] reported that MIE is cost-effective compared to open esophagectomy in the management of patients with resectable esophageal cancer. Due to its less invasiveness and safety, percent of MIE done for esophageal carcinoma is on rise in all world leading centers dealing with this pathology.…”
Section: Open Versus Minimally Invasive Esophagectomy a Current Dilemmamentioning
confidence: 99%